2011
DOI: 10.1007/s12574-011-0083-z
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic internal jugular vein thrombosis in a patient with severe dizziness

Abstract: Upper torso deep vein thrombosis usually occurs in association with an indwelling venous catheter and/or malignancy as part of a paraneoplastic syndrome. However, idiopathic internal jugular vein thrombosis is a rare but potentially fatal condition. We report a 59-year-old woman who presented with severe dizziness. Ultrasonography and contrast-enhanced multislice computed tomography revealed thrombi in the left internal jugular vein. This patient had no malignancy, coagulation disorder, or infection. A ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The veins of the semicircular canal form a vein of the vestibular aqueduct and drain into the sigmoid sinus. Therefore, thrombosis of the sigmoid sinus or internal jugular vein can produce venous overload and congestion of the inner ear 11) reported a case of dizziness presenting as acute unilateral vestibulopathy in CVST, and Honma, et al 12) reported a case of severe dizziness induced by idiopathic internal jugular vein thrombosis. Second, IICP induced by CVST may affect the pressure of the inner ear endolymph.…”
Section: Discussionmentioning
confidence: 99%
“…The veins of the semicircular canal form a vein of the vestibular aqueduct and drain into the sigmoid sinus. Therefore, thrombosis of the sigmoid sinus or internal jugular vein can produce venous overload and congestion of the inner ear 11) reported a case of dizziness presenting as acute unilateral vestibulopathy in CVST, and Honma, et al 12) reported a case of severe dizziness induced by idiopathic internal jugular vein thrombosis. Second, IICP induced by CVST may affect the pressure of the inner ear endolymph.…”
Section: Discussionmentioning
confidence: 99%
“…All cases with a diagnosis of internal jugular vein thrombosis (with or without clinical signs), were included in this report [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. We excluded cases if the abstracts had deficient clinical data.…”
Section: Methodsmentioning
confidence: 99%